2018
DOI: 10.1159/000492271
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Morphological Characterization of a Neurodevelopmental Disorder-Related Mono-ADP-Ribosylhydrolase, MACRO Domain Containing 2

Abstract: MACRO Domain Containing 2 (MacroD2) is a neurodevelopmental disorder-related mono-ADP-ribosylhydrolase. Molecular features of this protein in neural tissues are largely unknown. In this study, we generated a specific antibody against MacroD2, and carried out expression and morphological analyses of the molecule during mouse brain development. In Western blotting, 2 MacroD2 isoforms with molecular masses of ∼70 and ∼75 kDa started to be expressed at embryonic day 16.5, reached the maximal level at postnatal day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…These mostly pathoneurological phenotypes of the MacroD2 gene are associated with its loss of function, thus suggesting a physiological role in the central nervous system. This correlates with robust neuronal expression of MacroD2 during brain development (Ito et al 2018).…”
Section: Macrod1 and Macrod2supporting
confidence: 54%
“…These mostly pathoneurological phenotypes of the MacroD2 gene are associated with its loss of function, thus suggesting a physiological role in the central nervous system. This correlates with robust neuronal expression of MacroD2 during brain development (Ito et al 2018).…”
Section: Macrod1 and Macrod2supporting
confidence: 54%
“…This is larger than the predicted molecular weight of the canonical MACROD2 isoform and might represent effects of particular amino acid sequences or posttranslational modification(s). A recent study revealed specific expression of MacroD2 in cortical and hippocampal neurons in the mouse brain 50 , agreeing with our findings of relatively high MACROD2 expression in human neuroblastoma cells. Together, these data show that the three hydrolases are expressed in different tissues.…”
Section: Macrod1 Macrod2 and Targ1 Are Differentially Expressed Thesupporting
confidence: 93%
“…However, it was not tested whether the identified compound might inhibit one of the macrodomains with catalytic activity [69]. [40,70,71] Ubiquitous expression, enriched in skeletal muscle [70,71] mRNA expression is induced by oestrogen [72][73][74] MACROD2 C20orf133 MACROD2 47 kDa 50 kDa [70] Diffuse nuclear, cytoplasmic [70,75] So far detected only in the brain [70,76] Phosphorylation by ATM upon DNA damage induces translocation to cytoplasm [75] TARG1 C6orf130 OARD1 17 kDa 17 kDa [14,70] Nuclear, nucleolar, stress granular [14,45,70] Ubiquitous expression [70] Leaves nucleoli upon DNA damage [14] * The predicted molecular weight of MACROD1 is 35 kDa. However, due to cleavage of the N-terminus upon translocation into mitochondria, the protein detected in western blotting (WB) is smaller [70].…”
Section: Macrodomain-containing Hydrolases: Macrod1 Macrod2 and Targ1mentioning
confidence: 99%
“…TARG1 and MACROD1 are expressed throughout the different tissues with an enrichment of MACROD1 in skeletal muscle at both the protein and RNA level [70]. MACROD2 has, thus far, only been detected in human neuroblastoma cells and in mouse cortical neurons [70,76]. Several reports have correlated polymorphisms or deletions within the MACROD2 gene with autism-spectrum disorders [77][78][79][80].…”
Section: Macrodomain-containing Hydrolases: Macrod1 Macrod2 and Targ1mentioning
confidence: 99%
See 1 more Smart Citation